The Role of Implicature and Presupposition in Men’s and Women’s Manipulative Utterances - Sorokina, Lina Ye.; Сорокіна, Ліна Євгеніївна (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2016)
The article deals with a research of verbal mechanisms of manipulative utterance organization, in particular implicature and presupposition. A characteristic feature of manipulative message is deliberate formation of an implicit content. Special attention is given to the gender aspect of manipulative influence. In our corpus of samples implicit manipulative mechanisms are mostly applied by men in order to make threats or reproaches. Форма маніпулятивного повідомлення розуміється як спосіб організації інформації, яка зазнає викривлення. Головною характерною рисою маніпулятивного висловлення є навмисність породження імпліцитного змісту. Характерною рисою маніпулятивного висловлення є навмисність породження імпліцитного змісту. До засобів імпліцитної передачі інформації з метою маніпуляції у більшості випадків удаються чоловіки, як правило, імплікуючи докір або погрозу.
Роль імплікації та пресупозиції у маніпулятивних висловленнях чоловіків та жінок
Роль импликации и пресуппозиции в манипулятивных высказываниях мужчин и женщин
Keywords: verbal manipulation; manipulative utterance; implicature; presupposition; мовленнєва маніпуляція; мовленнєве висловлення; імплікація; пресупозиція